STUDI DALAM KAJIAN AL-SUNNAH - Gusmawati Gusmawati; Sri Suci (Adisam Publisher, 2025)
Al-Sunnah is the spirit of life and life of Muslims, and this has been recognized and confirmed by the Koran. In fact, not only that, the sunnah is used as the second source of law, so it is impossible for someone to only adhere to the Qur'an without adhering to the sunnah or what is often called inkar al-sunnah, because the sunnah has a very strong relationship, connection and bond. and solid with the Qur'an, it is proven that the sunnah is used as an explanation for the interpretation of the Qur'an, revealing a multitude of secrets of the essence of the meaning of the Qur'an and explaining what Allah desires in His word (Muhammad al-'Alawiy, 2008: 10 – 13). This journal tries to discuss the Al-Sunnah Study Area, Position and Function of Al-Sunnah, Methods of Understanding Al-Sunnah. The approach method used in this discussion is a literature review which is taken according to the subject of discussion and analyzed in depth so that it can be taken into account in the future.